Ecology of the Slug, Girasia crocea (Godwin-Austen) (Stylommatophora : Ariophantidae) (Journal of Environmental Science and Natural Resources, 2015)
Slug Girasia crocea (Godwin-Austen) is an herbivore, feeds on soft twigs or leaves of plants. The slug G. crocea are active for period of March-November. They use to overcome winter month (December-February) through hibernation. Sometimes they were seen to winter morning. In nature, they have a wide range of food acceptability. The feeding and foraging activities are confined to night ours. In nature, breeding period extends from March to November. The egg laying and other breeding activities are maintained at an equal temperature during the whole active period. In laboratory, they thrived well on Amranthus sp. And Spinacea sp., while temperature. They attained adult at the age of 196 days to 201 days. They lay eggs lay in cluster. The eggs are round in shape and white in colour. Individual slugs on an average, added 9.5mm, 2.5mm and 40mg; 13.5mm, 3.5mm and 40mg; 17mm, 5mm and 50mg; 24mm, 5mm and 60 mg; 35.5mm, 6 mm and 485mg; 52mm,10mm and 1190mg; 65mm, 8.5 and 1114mg; 65mm, 9.5mm and 1117mg and 57mm, 10mm and 1134mg to their body length, body width and body weight respectively at temperature of 26 - 31.50C during the study period. On an average an egg was measured 3.85mm in diameter.DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22071 J. Environ. Sci. & Natural Resources, 6(1): 227-232 2013